Violence in Islamic Thought From European Imperialism to the Post-Colonial Era - Edited by Mustafa Baig and Robert Gleave (Edinburgh Edinburgh University Press, 2022)
This volume shows the diversity of approaches to violence in Islamic thought between the 19th century and the present day, avoiding the limiting characterisations of Islam being inherently 'violent' or 'peaceful'.
Include Bibliography and Index
Keywords: Violence--Religious aspects--Islam -- Violence--Religious aspects -- Religion -- Islam